Finite-element analysis and design of stainless-steel CHS-to-SHS hybrid tubular joints under axial compression. (June 2020) - Feng, Ran; Huang, Zhipeng; Chen, Zhenming; Roy, Krishanu; Chen, Boshan; Lim, James B.P.
Abstract: This paper presents a finite-element (FE) investigation of the load-carrying capacities of stainless-steel CHS-to-SHS hybrid tubular T/Y- and X-joints. The non-linear finite-element models (FEMs) were developed and validated against the test results available in the literature, which were then used to conduct an extensive parametric study comprising 144 FEMs for T/Y-joints and 144 FEMs for X-joints. The purpose of the parametric study was to investigate the effects of critical geometric parameters of brace diameter-to-chord width ratio ( β  =  d 1 / b 0 ), brace-to-chord thickness ratio ( τ  =  t 1 / t 0 ), chord width-to-thickness ratio (2 γ  =  b 0 / t 0 ) and the angle between the centre line of brace and chord ( θ ). The suitability of the different stainless-steel constitutive models available in the literature, was verified against the stress-strain curves obtained from the tests. The results of the parametric study showed that the load-carrying capacities of tubular joints were affected by the geometric parameters, being especially sensitive to the value of β . Furthermore, the load-carrying capacities obtained from the parametric study were compared against the design strengths calculated from the current design guidelines. The comparison shows that the current design rules are not appropriate for predicting the load-carrying capacities of stainless-steel CHS-to-SHS hybrid tubular T/Y- and X-joints. Therefore, the modified design formulae are proposed in this paper, which were developed based upon the current design formulae of CIDECT. Highlights: FEA was performed on stainless-steel CHS-to-SHS hybrid tubular T/Y- and X-joints. A parametric study was carried out on 288 FEMs to investigate the effects of critical geometric parameters. The Rasmussen and Quach models were used to represent the CHS brace and SHS chord materials, respectively. CIDECT, EC3, GB 50017 and AS/NZS are not appropriate for stainless-steel CHS-to-SHS hybrid tubular T/Y- and X-joints. Proposed design formulae can accurately predict the load-carrying capacities of stainless-steel CHS-to-SHS hybrid tubular joints.